Persepsi User dan Preparer Laporan Keuangan Terhadap Pelaporan Sosial Perbankan Islam di Malaysia - Rifqi Muhammad (Jurnal Akuntansi dan Auditing Indonesia, 2010)
An Islamic bank is a unique institution because they do not only focus on economic matters but also on their social roles to their society. However, their social roles might not be exposed extensively due to the lack of disclosures. Haniffa (2002) proposed Islamic Social Reporting as the alternative to fill this gap. Islamic Social Reporting is the process of identifying, providing, and communicating social and other relevant information in conformity with the spiritual need of Muslims decision makers in order to demonstrate accountability to God and community; to increase transparency of business activities toward Muslim Ummah; and to achieve Mardātillah (blessing from Allah). This study aims to investigate the users’ and preparers’ of financial statements of Islamic social reporting by Islamic banks in Malaysia since this country is in the forefront on the development of Islamic banking and finance. This study specifically examines the stakeholders' perceptions on two issues of Islamic Social Reporting: (a) the objectives of Islamic social reporting; and (b) the information that might be useful for the stakeholders and society. It involves some stakeholders such as Islamic banks' accountants, members of Sharī’ah Supervisory Board (SSB), Muslim accounting Academicians, and customers that are proxies by postgraduate students. This study adopts the questionnaire survey method to examine the perceptions of stakeholders. The study found that the stakeholders of Islamic banks in Malaysia have positive views on Islamic social reporting. This study may contribute to the improvement of Islamic banking reports and to increase the awareness of regulator and management of the social roles of Islamic banks particularly in Malaysia and widely practiced in the Islamic financial industry in the world. Keywords: Islamic banks, Islamic social reporting, Islamic accountability